2013
DOI: 10.1186/1755-8794-6-5
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal role of the muscle-contraction pathway in cryptorchidism and evidence for genomic connections with cardiomyopathy pathways in RASopathies

Abstract: BackgroundCryptorchidism is the most frequent congenital disorder in male children; however the genetic causes of cryptorchidism remain poorly investigated. Comparative integratomics combined with systems biology approach was employed to elucidate genetic factors and molecular pathways underlying testis descent.MethodsLiterature mining was performed to collect genomic loci associated with cryptorchidism in seven mammalian species. Information regarding the collected candidate genes was stored in MySQL relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 88 publications
0
27
1
Order By: Relevance
“…Other important issues that need clarification are the genetic and ethnic background, which could influence circadian rhythms and seasonal patterns, even if this study found that the pattern of a summer shift can be observed in different ethnic and genetic backgrounds. Discovering molecular pathways associated with diseases plays a pivotal role in understanding the relation between cardiological pathologies and genetic factors 37. We hope our findings will represent a convincing starting point for future studies to elucidate the molecular control factors and mechanisms behind these and even more complicated seasonal/circadian physiopathological phenomena, and we posit they could well have clinical implications on prognosis and treatment of cardiovascular disease 38…”
Section: Discussionmentioning
confidence: 77%
“…Other important issues that need clarification are the genetic and ethnic background, which could influence circadian rhythms and seasonal patterns, even if this study found that the pattern of a summer shift can be observed in different ethnic and genetic backgrounds. Discovering molecular pathways associated with diseases plays a pivotal role in understanding the relation between cardiological pathologies and genetic factors 37. We hope our findings will represent a convincing starting point for future studies to elucidate the molecular control factors and mechanisms behind these and even more complicated seasonal/circadian physiopathological phenomena, and we posit they could well have clinical implications on prognosis and treatment of cardiovascular disease 38…”
Section: Discussionmentioning
confidence: 77%
“…Disease comorbidity has been also reported, for instance, cryptorchidism is also commonly associated to hypospadias and micropenis (Klonisch et al, 2004). Additionally, a molecular explanation for co-presence of cryptorchidism and cardiomyopathy; frequent clinical features co-present in RASopathies has also been proposed (Cannistraci et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Diverse candidate genomic variations involved in cryptorchidism development have been reported and 217 genomic variations from seven mammalian species (human, horse, sheep, dog, cattle, rat, and mouse) were cataloged in our previously developed Cryptorchidism gene database (CryptoGene DB) (Cannistraci et al, 2013). A comparative approach is important when researching complex diseases such as cryptorchidism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering risks of transmitting an abnormal paternal genotype to the descendant, an appropriate database would enable the quantification of such risks. Similarly, we have developed catalogs of genomics data in other fields, for instance molecular mechanisms involved in cryptorchidism development [Cannistraci et al 2013]. Standardization of reporting may be necessary when combining data sets from several manuscripts.…”
Section: Introductionmentioning
confidence: 99%